Surgical oncology operative experience at a high‐volume safety‐net hospital during the COVID‐19 pandemic. Issue 7 (22nd July 2021) - Kronenfeld, Joshua P.; Collier, Amber L.; Choi, Seraphina; Perez‐Sanchez, Dayana; Shah, Ankit M.; Lee, Christina; Goel, Neha
Abstract: Background: The coronavirus (COVID‐19) pandemic led to disruptions in operative and hospital capabilities as the country triaged resources and canceled elective procedures. This study details the operative experience of a safety‐net hospital for cancer‐related operations during a 3‐month period at the height of the pandemic. Methods: Patients operated on for or diagnosed with malignancies of the abdomen, breast, skin, or soft‐tissue (September 3, 2020–September 6, 2020) were identified from operative/clinic schedules. Sociodemographics, tumor and treatment characteristics, and COVID‐19 information was identified through retrospective chart review of a prospectively maintained database. Descriptive statistics were calculated. Results: Fifty patients evaluated within this window underwent oncologic surgery. Median age was 61 (interquartile range: 53–68), 56% were female, 86% were White, and 66% were Hispanic. The majority (28%) were for colon cancer. Only two patients tested positive for COVID‐19 preoperatively or within 30 days of their operation. There were no mortalities during the 1‐year study period. Conclusion: During the COVID‐19 pandemic, many hospitals and operative centers limited interventions to preserve resources, but oncologic procedures continued at many large‐volume academic cancer centers. This study underscores the importance of continuing to offer surgery during the pandemic for surgical oncology cases at safety‐net hospitals to minimize delays in time‐sensitive oncologic treatment.